0072 Oil mist, from exposure determinants to early effect markers: an integrative study design. (21st August 2017) - Hulo, Sébastien; Bourgkard, Eve; Sauvain, Jean-Jacques; Demange, Valérie; Hopf, Nancy; Guichard, Yves; Jeandel, Fanny; Edmée, Jean-Louis; Chérot, Nathalie; Wild, Pascal
Abstract : The present project focuses on the effects of occupational exposure to oil mists on a panel of exposure and effect biomarkers in an epidemiological study. The assumption is that different health outcomes are caused by reactive particles causing oxidative stress leading to lung inflammation and ultimately cancer or asthma. Ninety workers from France and Switzerland (30 controls, 30 exposed to straight cutting oil and 30 to soluble cutting oil) will be followed over two days after a non-exposed period of at least two days. The exposure assessment is based on measurements of particles, metals, aldehydes, amines, the intrinsic oxidative potential of aerosols and the cutting oil. Furthermore, exposure biomarkers are measured in exhaled breath condensate (EBC)- metals, ions (nitrite, nitrate...) and urine –metals, metabolites of PAHs- . Finally, exposure determinants will be collected to guide future efforts in exposure prevention. Effect biomarkers of oxidative stress (malondialdéhyde, 8-isoprostane, 8-hydroxy-2'-deoxyguanosine) in EBC and urine will be repeatedly measured as well as exhaled nitric oxide (FeNO), an inflammation marker. Genotoxic effects will be assessed using the buccal micronucleus cytome assay. Finally, the possible chronic effects of oil mist exposure on respiratory health will be explored by standard questionnaires. This integrative project will gain insights in the exposure determinants that drive the physiopathological effects, thus allowing an efficient prevention strategy to be developed.